Mencari Kecukupan Dalam Dunia Yang Materialistis: Analis Teologis Terhadap Konsep Kecukupan Dalam Surat Ibrani - Putra, Henry (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
This study aims to examine the concept of sufficiency in the Letter to the Hebrews and its relevance in facing the challenges of materialism in the modern era. The method used is a qualitative approach with theological analysis, including a literature study of the Bible text (especially Hebrews 13:5-6), theological commentaries, and related literature. The results of the study indicate that true sufficiency in the perspective of the Letter to the Hebrews is centered on faith and dependence on God, not on material wealth. This teaching offers a solution for spiritual life amidst the pressures of a consumer culture by emphasizing satisfaction in Christ, a simple lifestyle, and hope in God's promises. The practical implications include the role of the church in teaching the principle of biblical sufficiency through teaching, congregational development, and programs that encourage a life of sharing and gratitude. In conclusion, this study confirms that Christian faith is a solid foundation for finding true sufficiency, while providing strategic recommendations for the church and individuals in implementing these values ??in a materialistic world.